Quantification of key developmental risks in Africa - Bakhtina, V.; Zgurovsky, M. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2008)
Current research identifies six key developmental risks for Africa: (a) vulnerability of infrastructure, (b) health, (c) education, (d) political and security risk, (e) vulnerability to natural disasters and (f) limitation of access to drinking water and sanitary facilities. Key risks are combined to an integrated risk measure and their impact on 42. African countries is analyzed. Six countries most susceptible to the indicated set of risks are isolated.